2022
DOI: 10.3390/app121910044
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Hip Abductor Muscle Strength and Frontal Plane Kinematics: A Cross-Sectional Study in Elite Handball Athletes

Abstract: Frontal plane kinematics of the lower limb could be especially relevant in the risk of injuries in handball (HB) athletes. An association between lower limb frontal plane kinematics and hip abductor muscles strength has been investigated in different populations. However, the relationship between pelvis, hip, and knee frontal plane kinematics and the hip abductor strength in HB athletes has not been considered. Therefore, the objective of this study was to evaluate the relationship between hip abductor muscles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…While it would be ideal to compare the beta application based on computer vision with a 3D analysis system such as the ©VICON Motion System from Oxford, UK, the similarity of the results with previous studies that have compared traditional 2D analysis with 3D analysis systems (which reported SEM values ranging from 2 • to 5 • ) is encouraging [32]. The findings of the present study also showed that the knee valgus angle values observed in elite handball athletes during a singleleg squat were lower than those reported in other studies with elite handball athletes [10]. However, it is important to note that the study did not focus on describing the knee valgus or its relationship with injury risk.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…While it would be ideal to compare the beta application based on computer vision with a 3D analysis system such as the ©VICON Motion System from Oxford, UK, the similarity of the results with previous studies that have compared traditional 2D analysis with 3D analysis systems (which reported SEM values ranging from 2 • to 5 • ) is encouraging [32]. The findings of the present study also showed that the knee valgus angle values observed in elite handball athletes during a singleleg squat were lower than those reported in other studies with elite handball athletes [10]. However, it is important to note that the study did not focus on describing the knee valgus or its relationship with injury risk.…”
Section: Discussionsupporting
confidence: 88%
“…Several authors measured the reliability of Kinovea by assessing the lower limb kinematics in frontal and sagittal planes, which showed excellent values. Thus, Kinovea seems to be a free, portable, and easy-to-use software that may be used by clinicians and researchers [10,[12][13][14][15]27].…”
Section: Knee Valgus Angle Measurement With the Kinovea Softwarementioning
confidence: 99%
See 2 more Smart Citations